2022
DOI: 10.3390/brainsci12040484
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effects of Transcranial Direct Current Stimulation on Tinnitus, Depression, and Anxiety: A Systematic Review

Abstract: (1) Background: Tinnitus is the awareness of a sound in the absence of an external source. It affects around 10–15% of people, a significant proportion of whom also experience symptoms such as depression or anxiety that negatively affect their quality of life. Transcranial direct current stimulation (tDCS) is a technique involving constant low-intensity direct current delivered via scalp electrodes. It is a potential treatment option for tinnitus, as well as tinnitus-related conditions such as depression and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
4
1
1
Order By: Relevance
“…Anxiety was included in this study because the same area used for cognitive stimulation has been shown to be effective in improving neuropsychiatric symptoms [26]. However, unlike other studies [35,36], our findings did not show significant improvements in anxiety. We attribute this outcome to the deliberate selection of older individuals without a previous history of psychiatric disorders and who only exhibited "possible symptoms of anxiety", as indicated by their HADS scores.…”
Section: Discussioncontrasting
confidence: 67%
“…Anxiety was included in this study because the same area used for cognitive stimulation has been shown to be effective in improving neuropsychiatric symptoms [26]. However, unlike other studies [35,36], our findings did not show significant improvements in anxiety. We attribute this outcome to the deliberate selection of older individuals without a previous history of psychiatric disorders and who only exhibited "possible symptoms of anxiety", as indicated by their HADS scores.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the highly unstable electrode montage in the tDCS study may make the results inaccurate. The outcomes of a previous meta-analysis on the duration and length of tDCS sessions offer us an opportunity to further optimize this intervention (Labree et al, 2022 ). Relevant studies (Narita et al, 2017 ) also demonstrate the efficacy of the designed controlled trial for evaluating the effect of tDCS on the treatment of PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Several excellent related narrative or systematic reviews have recently been published. [28][29][30][31][32][33] However, these reviews inevitably lose some information of this theme due to exclusion of unqualified studies or the limited scope. Therefore, this review sought to bring together the continuous work from the literature and summarize the existing types of non-invasive electrical stimulation (NIES) and their application value in tinnitus treatment without excluding studies based on their quality.…”
Section: State Of the Art: Non-invasive Electrical Stimulation For Th...mentioning
confidence: 99%